2011
DOI: 10.1093/infdis/jiq078
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Expression of Human T-lymphotropic Virus Type 1 Basic Leucine-Zipper Protein Generates Specific CD8+ and CD4+ T-Lymphocyte Responses that Correlate with Clinical Outcome

Abstract: HBZ protein is expressed in vivo in patients with HAM and in ACs. Our results are consistent with the idea that the T cell response to HBZ plays an important part in restricting HTLV-1 viral load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 36 publications
2
78
0
Order By: Relevance
“…This observation supports our hypothesis. An earlier study (36) reported that HBZ-specific T cell responses were detected in some patients with HTLV-1-associated myelopathy (HAM). Unlike ATL, HAM can occur in individuals infected with HTLV-1 by any route of transmission, such as sexual intercourse (37).…”
Section: Discussionmentioning
confidence: 99%
“…This observation supports our hypothesis. An earlier study (36) reported that HBZ-specific T cell responses were detected in some patients with HTLV-1-associated myelopathy (HAM). Unlike ATL, HAM can occur in individuals infected with HTLV-1 by any route of transmission, such as sexual intercourse (37).…”
Section: Discussionmentioning
confidence: 99%
“…At the same way as for Tax, HBZ-specific CD8+ T cell response appears to be important to maintain low proviral load and asymptomatic status of carriers (Hilburn et al, 2011).…”
Section: Ham/tspmentioning
confidence: 99%
“…The ability of an individual's HLA-alleles to bind peptides from HBZ has been shown to correlate inversely with proviral load and risk of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) [11]. Despite its significant protective potential, the binding affinity of HBZ peptides to HLA class I molecules was found to be significantly weaker than that of peptides from Tax, and the frequency of HBZ-specific CD8 + T cells in peripheral blood was extremely low [11,12], although the IL-2 secreting HBZ-specific CD8 + T cells were more frequently detected in individuals with a viral load of below 1% of PBMCs [12]. In addition, HBZ protein is present at levels barely detectable by western blot; inefficient polyadenylation and transport of mRNA from the nucleus are thought to be responsible for this low expression [4,[13][14][15].…”
Section: Htlv-1-infected Autologous Cd4mentioning
confidence: 99%